The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1073/pnas.0914299107
|View full text |Cite
|
Sign up to set email alerts
|

Circadian control of carbohydrate availability for growth inArabidopsisplants at night

Abstract: Plant growth is driven by photosynthetic carbon fixation during the day. Some photosynthate is accumulated, often as starch, to support nocturnal metabolism and growth at night. The rate of starch degradation in Arabidopsis leaves at night is essentially linear, and is such that almost all of the starch is used by dawn. We have investigated the timer that matches starch utilization to the duration of the night. The rate of degradation adjusted immediately and appropriately to an unexpected early onset of night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
738
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 576 publications
(815 citation statements)
references
References 41 publications
41
738
1
8
Order By: Relevance
“…Given that transitory starch degradation is under circadian control (Graf et al, 2010), these results suggests that starch degradation in submerged plants is preserved both at the level of regulation and enzymatic efficiency, although we cannot exclude that differences exist in the mechanism operating under submergence. Remarkably, the energy-requiring step catalyzed by GWD was required for starch degradation under submergence (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Given that transitory starch degradation is under circadian control (Graf et al, 2010), these results suggests that starch degradation in submerged plants is preserved both at the level of regulation and enzymatic efficiency, although we cannot exclude that differences exist in the mechanism operating under submergence. Remarkably, the energy-requiring step catalyzed by GWD was required for starch degradation under submergence (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…This "starvation response" is seen, for example, when the night is extended beyond the normal dawn and in mutants defective in the storage or utilization of starch reserves during the night (Smith and Stitt, 2007). The starvation response can be monitored by measuring transcript levels of genes for which expression is known to be specifically responsive to carbohydrate levels (Gibon et al, 2004;Bläsing et al, 2005;Osuna et al, 2007;Usadel et al, 2008;Graf et al, 2010). We investigated whether the reduced carbohydrate levels in the terminal cluster of flowers and buds of gsl7 inflorescences triggered a starvation response by determining the expression of four starvation-induced genes (At1g76410, At3g59940, At1g08630, and At1g10070) and one sugar-induced gene (At3g13470; Supplemental Table S4).…”
Section: Phloem Transport Rates and Carbohydrate Availability Are Redmentioning
confidence: 99%
“…Mutant Arabidopsis thaliana plants that fail to synthesize or degrade starch in the leaves have reduced growth rates under most conditions (Yazdanbakhsh and Fisahn, 2011;Usadel et al, 2008b). This nearly linear pattern of starch biosynthesis and degradation is retained under changing photoperiods or if plants are subject to a sudden early or late dusk, as long as the total circadian rhythm remains at 24 h (Sulpice et al, 2014;Graf et al, 2010). It is indeed observed that plants degrade starch faster in long days than in short days, demonstrating that plants somehow anticipate the length on the following night (Gibon et al, 2004;Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%